Improving Village Administrative Efficiency through the Use of a Correspondence Management Information System: A Case Study of Namorambe Village - Dybio Dompu Hot Asih; Alex Karo-Karo (Sah Publisher, 2026)
Village administrative services play a crucial role in supporting effective governance and responsive public service delivery. However, many village administrations still manage correspondence manually, resulting in inefficiencies, data duplication, limited document accessibility, and delays in administrative services. This community service activity aims to improve village administrative efficiency through the implementation of a Correspondence Management Information System in Namorambe Village. The activity was conducted using several stages, including problem identification and needs assessment, system design and development, system implementation, and training for village officials. The developed system facilitates the digital management of incoming and outgoing correspondence, document archiving, search functions, and administrative reporting in a centralized database. Training and hands-on assistance were provided to ensure that village officials were able to operate and manage the system independently. The results of the implementation indicate a significant improvement in the efficiency of administrative processes, particularly in reducing the time required to manage and retrieve correspondence documents. In addition, the accuracy and security of administrative data improved due to structured digital storage. Village officials also demonstrated increased digital competence and readiness to adopt information technology in daily administrative tasks. Overall, this community service activity demonstrates that the utilization of a correspondence management information system can effectively support village administrative efficiency and contribute to the digital transformation of village governance. The system has the potential to be sustainably adopted and replicated in other villages with similar administrative challenges.